Effect of spermine and cyclohexylamine on in vitro pollen germination and tube growth in Helianthus annuus - (:unkn) unknown (AGR INST CANADA, 2000)
Naturally occurring polyamines (PA) are known to play a key role in growth and development of plants and animals. However, the role of these polycations in the development and germination of the pollen grain is not well understood. The effect of different concentrations of spermine (Spm) on pollen tube growth in Helianthus annuus was investigated. Spermine treatments in the 10(-7) to 10(-5) M range stimulated pollen tube growth starting in the first 15 min of the incubation period, while 10(-4) M Spm treatment resulted in inhibition of pollen tube elongation. The effect of cyclohexylamine (CHA), an inhibitor of Spm synthesis on pollen tube growth and germination percentage was also studied. Cyclohexylamine in the 0.5 x 10(-3) M to the 1.5 x 10(-3) M range inhibited pollen tube elongation. The relationship of B deficiency, excess B and PA effect on pollen germination and pollen tube growth were also investigated.
Keywords: polyamines; pollen; cyclohexylamine; boron; POLYAMINES; PHYSIOLOGY